A expansão da educação superior na região Oeste do Paraná e suas influências no grau de formação dos professores universitários - Heringer, Eudiman (2017)
The expansion of the offer of higher education in Brazil, especially since the 1990s, has promoted economic and social impacts in the different Brazilian regions. It is an educational policy to meet a historically repressed demand and gives a large part of young Brazilians access to university education. This dissertation aims to know how the expansion of this type of education occurred in the western Meso-region of Paraná. To do so, we used data from the National Institute of Educational Studies and Research Anísio Teixeira - INEP for a more recent period available, between 2009 and 2012. Integrating the study, a bibliographical research was also conducted in authors who discuss and follow the education policy on higher education, such as SGUISSARDI (2008), DIAS SOBRINHO (2014), MANCEBO (2015), among others, as well as relevant documentary data and updated. The text consists of a discussion about the expansion of proper higher education, followed by tables with informative data in representative aspects and referring to the theme. To better illustrate the study, we differentiate into three microregions: Cascavel, Foz do Iguaçu and Toledo that are part of the western mesoregion of the state. The observed aspects reveal some specificities that refer us to the continuation of the analysis because they are given, for example, as for the increases and decreases of enrollments in some areas. Highlighted, we find the existence of qualified teaching staff in ascension in the period.